Removal of Lead from Synthetic Solutions by Protonated Teleosts Biomass. Issue 1 (2012) - Aqeel Ashraf, Muhammad; Jamil Maah, Mohd.; Yusoff, Ismail
Abstract : Lead is considered as a general protoplasmic poison which is cumulative and slow acting. It is used in different industrial processes. Its contamination in water may cause serious environmental problems. So removal of lead from environment is very necessary. For its removal the most suitable and cheapest process is biosorption. It is a process of passive metal binding by biomass. The biosorbent used in this study is teleosts biomass (fish scales) collected from local market. The purpose of this study is to search the effect of acid treatment on biosorbent and to optimize conditions for the uptake capacity of biosorbent. The optimal conditions for the Pb 2+ biosorption capacity of teleosts biomass (fish scales as waste of white meat) was investigated. For this purposes, the biomass was subjected to chemical treatments with mono, di and tri-protic acids such as hydrochloric acid, sulphuric acid and phosphoric acid. Among the treatment methods used, the highest Pb 2+ uptake was obtained with hydrochloric acid treatment of biomass. The effect of pH, biomass granular size, biomass concentration and initial Pb 2+ ion concentration was studied. The highest Pb 2+ removal (65.39%) was obtained at pH 4.0 for 50 mg L −1 initial lead ion concentration with biomass granular size 80 micron and concentration of 0.05 g. The uptake was 75.70 mg g −1 . The equilibrium data were analyzed using the Langmuir and Freundlich adsorption isotherm. The characteristic parameters for each isotherm were determined. Both the isotherms provided the best correlation for Pb 2+ on to the biomass. These results showed that teleosts biomass (fish scales) is a potential biomass to remove Pb 2+ ions from synthetic solutions so also with lead contaminated water. These values can be compared with those observed for other biosorbents and it is considerably higher than the value obtained with the majority of the biosorbent.